Pengaruh Harga, Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Smartphone Merek Vivo (Studi pada Masyarakat Kecamatan Bontang Selatan yang Menggunakan Smartphone Merek Vivo) - Syamsumarlin Syamsumarlin; Muhammad Zaini (J-MAS (Jurnal Manajemen dan Sains), 2023)
Smartphones are not only a long-distance communication tool, but can do many things such as conducting business transactions, bank transactions (e-banking), and many others. Thus the smartphone becomes a new friend for people's lives, because there are so many conveniences offered. This study aims to determine the effect of price, product quality and brand image on purchasing decisions of Vivo brand smartphones in the people of South Bontang District. The method used in this study is a quantitative method with primary data obtained from distributing questionnaires. The sampling technique used purposive sampling using the Lemeshow formula, there were 100 respondents in this study. The analytical tool used in this study is multiple linear analysis with the help of SPSS 23 Statistical Software. The research hypothesis indicates that the independent variables namely price (X1), product quality (X2) and brand image (X3) simultaneously have a significant influence on the dependent variable. namely the purchase decision (Y). Partially, the price variable (X1) and brand image (X3) have a significant effect on the purchase decision variable (Y), while the product quality variable (X2) has no significant effect on the purchase decision variable (Y).